The Primo Vascular System Its Role in Cancer and Regeneration - Soh, Kwang-Sup.; Kang, Kyung A.; Harrison, David K.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
The first International Symposium on Primo Vascular System 2010 (ISPS 2010) with special topics on cancer and regeneration was held in Jecheon, Korea during September 17-18, 2010. The symposium dealt with the past findings, current status, and future prospect of the PVS research in the context of cutting-edge investigation in oriental and occidental medicine, molecular biology, and biophysics. This proceedings volume explores the first international opportunity to exchange the research results on PVS among multi-disciplinary experts. New study results have better revealed the functional aspects of PVS, including its roles in the areas of regenerative medicine and cancer. These research results have also suggested the extensive roles of PVS in humans, potentially changing the entire paradigm of medicine. The Primo Vascular System is a timely volume that will help accelerate many disciplines as it delves into this newly researched system.
Past, Present and Future of Primo Vascular System Research -- A Brief History of the Bong-Han Theory and the Primo Vascular System -- Summary of Bong-Han Kim$1 (Bs Publications -- Follow-up Study on the Morphological Characteristics in Bong-Han Theory: an Interim Report -- Recollection of Early Research on Primo Vascular System: Ultimate Implication of Bong-Han Theory -- Current State of Research on the Primo Vascular System -- Primo Vascular System Basic and Applied Research Outline -- The Primo Vascular System: Facts, Open Questions and Future Perspectives -- Primo Vascular System in Various Organs -- Structure of the Sinus in the Primo Vessel inside the Bovine Cardiac Chambers -- Finding a Novel Threadlike Structure on the Intra-abdominal Organ Surface of Small Pigs by Using In-vivo Trypan Blue Staining -- Observation of Primo Vascular System on Intestinal Fascia of Dogs -- Development of the Putative Primo Vascular System before the Formation of Vitelline Vessels in Chick Embryos -- Characterization of Primo Nodes and Vessels by High Resolution Light Microscopy -- Distribution of Primo Vessels in the Mesentery of a Mouse -- Primo Vessels in the Mesentery of Nude Mice -- Comparison of the Primo Vascular System with a Similar-looking Structure -- Effect of the Primo Vascular System on Liver Tissue Recovery after Irreversible Electroporation: a Preliminary Study -- Detection of the Primo Vessels in the Rodent Thoracic Lymphatic Ducts -- Histological Comparison of Primo Nodes in Abdominal Membrane and Lymph Nodes of Rat -- Visualization of the Primo Vascular System by Using Trypan Blue in the Subarachnoid Space of Rats -- Network of the Primo Vascular System in the Rat Hypodermis -- Primo Microcell (SanAl) and Stem Cells -- Identification and Characterization of Small Stem-like Cells in the Primo Vascular System of Adult Animals -- Membrane Mechanical Property of Primo Microcells -- Primo microcell in a Primo Node as a Possible Origin of Adult Stem Cells -- Budding Primo Microcells (Sanals) in a Culture Medium with Fertilized Egg Albumen and RPMI Medium -- Cancer -- Identification of Primo Vascular System in Murine Tumors and Viscera -- Molecular Compositional Differences of Primo and Lymphatic Vascular System in Murine Melanoma Models -- Using Human Observations to Gain Biologic Insights and New Treatments -- Translational Development of Therapeutic Vaccines for Lymphoma -- Oxygen Transport to Tumors: Pathophysiology and Clinical Implications -- Stress Responses of Pancreatic Cancer Cells and Their Significance in Invasion and Metastasis -- Human Urine Extract (CDA-2) Eliminates Cancer Stem-Like Cells and Inhibits Metastasis-Its Potential Role on the Microenvironment of Primo Vascular System -- Imaging, Oxygen, Physiology and Others -- Mapping PVS by Molecular Imaging with Contrast Agents -- Unusual Optical Properties of Collagen and Implications for the Primo Vascular System -- Basic Electrophysiological Properties of Cells in the Organ Surface Primo Vascular Tissues of Rats -- Effects of Cholinergic Drugs on Membrane Potential of Cells in Organ Surface Primo Nodes -- Apoptotic Cardiomyocyte Beating Detected with Spectrometer of Intensity Fluctuations -- PKA Activation in Cardiac Myocytes Affects the Voltage Dependence of Na-K ATPase Pump and Na-Ca Exchange Currents Differently -- Bioimaging of Stem Cells, Live Tissue and Whole Animals using Diversity Oriented Fluorescence Library Approach -- The Clinical Application of Optical Spectroscopy in Monitoring Tissue Oxygen Supply Following Cancer Treatment -- Acupuncture -- Oriental Medicine in Japan, Lymphology and Primo Vascular System -- From the Anatomical Discovery of Meridians and Collaterals to Fasciaology Theory -- An Evidence-based Review of Acupuncture as an Adjunctive Therapy in Comprehensive Cancer Care -- Thermal Characteristics of Moxibustion and its Implication to Primo Vascular System.-.s
Keywords: Medicine; Cancer research; Human physiology; Complementary medicine; Acupuncture; Biochemistry; Cell physiology; Biomedicine; Cancer Research; Acupuncture; Biochemistry, general; Complementary & Alternative Medicine; Human Physiology; Cell Physiology; Electronic books